Depressive symptoms related to low fractional anisotropy of white matter underlying the right ventral anterior cingulate in older adults with atherosclerotic vascular disease - Bijanki, Kelly R.; Matsui, Joy T.; Mayberg, Helen S.; Magnotta, Vincent A.; Arndt, Stephan; Johnson, Hans J.; Nopoulos, Peg; Paradiso, Sergio; McCormick, Laurie M.; Fiedorowicz, Jess G.; Epping, Eric A.; Moser, David J. (Frontiers in Human Neuroscience, 2015)
We sought to characterize the relationship between integrity of the white matter underlying the ventral anterior cingulate (vAC) and depressive symptoms in older adults with atherosclerotic vascular disease (AVD), a condition associated with preferential degeneration of the white matter. The ventral anterior cingulate was defined as including white matter underlying ventral Brodmann Area 24 and Brodmann Area 25, corresponding with the “subcallosal” and “subgenual” cingulate respectively. This region of interest was chosen based on the preponderance of evidence that the white matter in the region plays a critical role in the manifestation of depressive symptoms. Participants had current unequivocal diagnoses of AVD and were between 55 and 90 years old. Fractional anisotropy (FA) was used as an index of white matter integrity and organization. Whole-brain mean diffusivity (MD) was used as an index of global white matter lesion burden. Depressive symptoms were measured using the Symptom Checklist-90-Revised (SCL-90-R) Depression Scale. Depressive symptoms were significantly related to low FA in the right vAC (r=-.356, DF=30, p=.045) but not the left vAC (r=.024, DF=30, p=.896) after controlling for total brain MD (a statistical control for global white matter lesion burden). Further, depressive symptoms were significantly related to low FA in the right vAC (r=-0.361, DF=31, p=.039), but not the left vAC (r=.259, DF=31, p=.145) when controlled for the contralateral vAC FA. The correlation coefficients for this follow-up analysis were found to be significantly different between left and right vAC (Z=2.310, p=.021). Poor white matter health in the vAC may be a biological mechanism for depressive symptoms in older adults with vascular disease. Further studies may corroborate that the right vAC plays a unique role in depressive symptom manifestation in cases where the white matter is preferentially affected, as is the case in AVD. This could lead to future targeting of